(untitled) (Research, Society and Development, 2025)
Objective: To understand the epidemiological profile of leprosy in the municipality of Cuiabá (MT). Methods: This is a cross-sectional, descriptive epidemiological study based on data from the Notifiable Diseases Information System (SINAN) available in the DW WEB system (SES-MT). The study included all patients diagnosed with leprosy between 2020 and 2022. Incidence and relative frequency analyses were performed to determine the epidemiological profile of infected patients, considering variables such as classification, treatment regimen, clinical forms, degree of physical disability, and mode of detection. The Chi-square test and Fisher’s Exact test were used to verify possible associations, with a p-value < 0.05. Results: A total of 992 new cases were reported during the study period, with 2022 accounting for the highest number of notifications (43.04%). The mean age of patients was 47.15 years (standard deviation: 17.03 years). The diagnosed patient profile was predominantly male (52.12%), Black or Brown (74.84%), aged over 45 years (total: 59.68%), and with an educational level up to high school (total: 67.94%). The most common clinical form was Dimorphous (80.65%), detected through spontaneous demand (26.92%), with a 12-dose treatment regimen (89.31%), and most patients presented with a grade zero disability (19.35%). Conclusion: The study determined the disease incidence in the analyzed period and the profile of infected individuals.